322 Efficacy and safety of lebrikizumab in moderate-to-severe atopic dermatitis: 52-week results of two randomized, double-blinded, placebo-controlled phase 3 trials (ADvocate1 and ADvocate2). (25th January 2023) - Blauvelt, Andrew; Thyssen, Jacob P; Guttman-Yassky, Emma; Bieber, Thomas; Carrascosa, Jose Manuel; Simpson, Eric; Rosmarin, David; Elmaraghy, Hany; Meskimen, Eric; Natalie, Chitra R; Liu, Zhuqing; Xu, Chenjia; et al.
Abstract: Lebrikizumab (LEB) is a novel, high-affinity monoclonal antibody that selectively binds to interleukin (IL)-13. To evaluate the efficacy and safety of LEB monotherapy in patients with moderate-to-severe atopic dermatitis (AD) in two identical phase 3 trials ADvocate1 (ADv1) and ADvocate2 (ADv2). Patients who responded to LEB 250 mg every 2 weeks (LEB Q2W) at the end of the 16-week induction period were re-randomized in a 2 : 2 : 1 ratio to receive LEB Q2W, LEB 250 mg every 4 weeks (LEB Q4W) or placebo (LEB withdrawal) for an additional 36 weeks. Response, at week 16, was defined as achieving an IGA (0, 1) with a ≥2-point improvement or EASI75 and no use of rescue medication. Efficacy outcomes reported at week 52 included IGA (0, 1), EASI 75, ≥4-point reduction in Pruritis Numeric Rating Scale (NRS), EASI 90 and DLQI ≥4-point. Safety analysis was conducted on all patients who received ≥1 dose of LEB. Patients maintained IGA (0, 1) in LEB Q2W (ADv1, 75.8%; ADv2, 64.6%), LEB Q4W (ADv1, 74.2%; ADv2, 80.6%) and LEB withdrawal (ADv1, 46.5%; ADv2, 49.8%). Maintenance of EASI75 was, in LEB Q2W (ADv1, 79.2%; ADv2, 77.4%), LEB Q4W (ADv1, 79.2%; ADv2, 84.7%) and LEB withdrawal (ADv1, 61.3%; ADv2, 72.0%). For Pruritus NRS ≥4-point improvement from baseline, patients-maintained improvement in the LEB Q2W (ADv1, 81.2%; ADv2, 90.3%), LEB Q4W (ADv1, 80.4%; ADv2, 88.1%) and LEB withdrawal (ADv1, 65.4%; ADv2, 67.6%). Maintenance of EASI90 was, in LEB Q2W (ADv1, 66.1%; ADv2, 61.5%), LEB Q4W (ADv1, 66.6%; ADv2, 67.4%) and LEB withdrawal (ADv1, 45.5%; ADv2, 36.9%). DLQI ≥4-point improvement from baseline was LEB Q2W (ADv1, 64.0%; ADv2, 59.0%), LEB Q4W (ADv1, 62.7%; ADv2, 73.0%) and LEB withdrawal (ADv1, 57.7%; ADv2, 45.5%). TEAEs were reported by 58.1% (ADv1) and 67.8% (ADv2) LEB-treated patients at week 52. Serious adverse events were reported by 3.3% of ADv1 patients and 2.7% of ADv2 patients. In ADv1 and ADv2, 2.3% and 3.9% of patients reported an adverse event leading to treatment discontinuation, respectively. Both LEB Q2W and LEB Q4W maintained improvement in all reported outcomes for the treatment of moderate-to-severe AD through 52 weeks. The safety profile was consistent with previously published data.